Determinants of Use of Climate Change Adaptation Practices by Rice Farmers in Kebbi State, North-West Nigeria - Danlami Yakubu; Oladimeji Oladele (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego, 2021)
Rice productivity and sustainability are threatened by both biotic and abiotic stresses, the effects of which can be further aggravated by dramatic changes in global climate. The most viable option for rice farmers is to use climate change adaptation practices. This study therefore investigated the determinants of use of climate change adaptation practices among rice farmers in Kebbi State, North-West, Nigeria. Data were collected from a sample of 279 farmers selected using a multistage sampling procedure. The results of the data analysis revealed that the farmers used improved rice varieties, intercropping, recommended rates of fertilizers and other chemicals as climate change adaptation practices among others. Education, climate change awareness, and extension contact significantly influenced the use of climate change adaptation practices among the farmers. Other determinants of use of climate change adaptation practices among the farmers were years of cooperative membership, affordability, farming experience, weather information and farm size. It was concluded that use of climate change adaptation practices was determined by socioeconomic, institutional and technological characteristics. It is recommended among others that government policy should be geared towards encouraging the farmers especially the younger ones to acquire more formal education, larger farmlands and more climate change awareness.